TNF-α involvement in insulin resistance induced by experimental scorpion envenomation. - Aouatef Ait-Lounis; Fatima Laraba-Djebari (Public Library of Science (PLoS), 2012)
BACKGROUND: Scorpion venom induces systemic inflammation characterized by an increase in cytokine release and chemokine production. There have been few experimental studies assessing the effects of scorpion venom on adipose tissue function in vivo. METHODOLOGY/PRINCIPAL FINDINGS: To study the adipose tissue inflammation (ATI) induced by Androctonus australis hector (Aah) venom and to assess possible mechanisms of ATI, mice (n = 6, aged 1 month) were injected with Aah (0.45 mg/kg), toxic fraction of Aah (FTox-G50; 0.2 mg/kg) or saline solution (control). Inflammatory responses were evaluated by ELISA and cell sorting analyses in adipose tissue 45 minutes and 24 hours after injection. Quantitative real-time PCR was used to assess the regulation of genes implicated in glucose uptake. The titers of selected inflammatory cytokines (IL-1β, IL-6 and TNF-α) were also determined in sera and in insulin target tissues. The serum concentration of IL-1β rose 45 minutes after envenomation and returned to basal level after 24 hours. The pathophysiological effects of the venom after 24 hours mainly involved M1-proinflammatory macrophage infiltration in adipose tissue combined with high titers of IL-1β, IL-6 and TNF-α. Indeed, TNF-α was strongly induced in both adipose tissue and skeletal muscle. We studied the effects of Aah venom on genes implicated in insulin-stimulated glucose uptake. Insulin induced a significant increase in the expression of the mRNAs for hexokinase 2 and phosphatidylinositol 3-kinase in both skeletal muscle and adipose tissue in control mice; this upregulation was completely abolished after 24 hours in mice envenomed with Aah or FTox-G50. CONCLUSIONS/SIGNIFICANCE: Our findings suggest that Aah venom induces insulin resistance by mechanisms involving TNF-α-dependent Map4k4 kinase activation in the adipose tissue.